The Effectiveness of the Justice Policies of the Last Decade in Latin America - Ramos Rollón, Marisa (Revista del CLAD Reforma y Democracia, 2017)
Judicial reforms in Latin America in the last decade have quite different characteristics from those that were carried out in the preceding decades. Reforms have lost centrality in the political agenda, despite the depth of the problems in the sector. They have not been part of plans or comprehensive processes involving draft changes in the sector. In addition, they have been oriented primarily towards issues related to the effectiveness and efficiency and to promote alternative methods to conflict resolution. Instead, institutional reforms have been limited. Although there are hardly any data allowing to conduct an assessment of the impact of the same, through approximate indicators it is concluded that these reforms have generated very limited results. In addition, there are two elements that contribute to giving content to the low effectiveness of these policies: firstly, the actors involved in the design and implementation of policies, the consequent sharing of competencies between institutions and the difficulty of coordinating them for common objectives and comprehensive policy orientations; and secondly, the instability of political positions, which reveals the incompatibility between political times and the times that require this type of reforms.
Keywords: Justice Administration; Judicial Reform; Effectiveness; Latin America